"Social Media Recruitment: Trends, Tools, and Techniques for Successful Hiring" (International Journal of Food and Nutritional Sciences, 2022)
This paper aims to explore the trends, tools, and techniques of social media recruitment for effective hiring. It provides an overview of the materials and methods employed in utilizing social media platforms for talent acquisition, presents the results achieved through these methods, and engages in a detailed discussion on the implications and best practices for successful social media recruitment.